Long-Term Efficacy and Anticoagulation Strategy of Left Atrial Appendage Occlusion During Total Thoracoscopic Ablation of Atrial Fibrillation to Prevent Ischemic Stroke - Kim, Ju Youn; Jeong, Dong Seop; Park, Seung-Jung; Park, Kyoung-Min; Kim, June Soo; On, Young Keun (Frontiers in Cardiovascular Medicine, 2022)
Objectives Atrial fibrillation (AF) is associated with an increased ischemic stroke, and the left atrial appendage (LAA) represents the main source of thrombus formation. We evaluated the long-term efficacy of surgical thoracoscopic LAA occlusion during total thoracoscopic ablation of AF to prevent the stroke and anticoagulation strategy after surgery. Methods Patients who underwent total thoracoscopic ablation for AF, from February 2012 to May 2020, were included; Patients who did not receive LAA occlusion were excluded. We evaluated the development of thromboembolism in these patients. Results The total number of 460 patients [mean age, 57.1 ± 9.2 years; 400 (87.0%) males] were included in the study. The mean follow-up duration was 44.8 months. The mean CHA2DS2-VASc score was 1.9 ± 1.6. Median OAC duration was 109.5 days after the surgery, and the final number of patients who discontinued OAC were 411 (89.3%) in total. Anticoagulation discontinuation rate according to CHA2DS2-VASc score are as follows; (i) 0 = 99.0%; (ii) 1 = 98.2%; and (iii) ≥2 = 81.3%. The annualized incidence rate of ischemic stroke was 0.78%/year, showing a 73% risk reduction compared with the CHA2DS2-VASc predicted rate without anticoagulation. The hazard ratio for ischemic stroke according to previous stroke history was 1.5 [95% confidential interval (CI) 0.3–7.3, p = 0.62], and that of remnant LAA was 5.1 (1.2–20.9, p = 0.02). Conclusions Thoracoscopic LAA occlusion during total thoracoscopic ablation of AF was effective to prevent ischemic stroke. Most patients could discontinue OAC therapy after the procedure. Patients who had a residual trabeculated LAA, or peri-occluder pouch in follow-up CT need to maintain OAC therapy even after LAA occlusion.